Renoprotective effect of N-acetylcysteine depends upon the severity of the ischemia reperfusion injury - Watanabe,M. (2021)
Acute kidney injury (AKI) is a common complication in seriously ill patients, while renal ischemia-reperfusion (I/R) injury is the most frequent event in this oxidative renal injury. N-acetylcysteine (NAC) is a small molecule containing a thiol group that has antioxidant properties, promoting detoxification and acting directly as a free radical scavenger. In this study, the protective effect of NAC was investigated in short-term (30 min) and long-term (45 min) ischemic AKI. This was achieved via clamping of the renal artery for 30 or 45 min in Wistar rats to induce I/R injury. AKI worsened with a longer period of ischemia (45 compared to 30 min) due to probable irreversible damage. Preconditioning with NAC in short-term ischemia improved renal blood flow and increased creatinine clearance by reducing oxidative metabolites and increasing antioxidant capacity. Otherwise, NAC did not change these parameters in the long-term ischemia. Therefore, this study demonstrated that the period of ischemia determines the severity of the AKI, and NAC presented antioxidant effects in short-term ischemia but not in long-term ischemia, confirming that there is a possible therapeutic window for its renoprotective effect.